(untitled) (Bangladesh Journal of Otorhinolaryngology, 2010)
This cross sectional study was done in the Otolaryngology and Head-Neck Surgery Department of Banghabandhu Sheikh Mujib Medical University, Dhaka Medical College Hospital and Sir Salimullah Medical College Hospital during the period of September 2003 to February 2004. In this study 30 patients of sinonasal malignancy were studied and to observe the clinicopathological pattern of sinonasal malignancy. The diagnosis was made by detailed history, clinical, radiological and histopathological examinations. In this study majority of the patients were within 40 to 70 years of age (77%). Male to female ratio was 2.33:1. Majority of the malignancy came from maxillary sinuses 15(50.00%); ethmoidal sinuses were involved in 8(26.66%) cases, multiple sinuses were involved in 5(16.66%). Neck node metastases was found in 4(14%) cases. Squamous cell carcinoma was the most common histological type (70.00%); the other less common histological types were adenoid cystic carcinoma (06.66%), adenocarcinoma (06.66%), Non-Hodgkin’s lymphoma (06.66%), least frequent types were malignant fibrous histocytoma, transitional cell carcinoma, olfactory neuroblastoma. Key words: Sinonasal malignancy; clinicopathological study. DOI: 10.3329/bjo.v15i2.5058 Bangladesh J Otorhinolaryngol 2009; 15(2): 55-59